Deletion of Btg1 Induces Prmt1-Dependent Apoptosis and Increased Stemness in Shh-Type Medulloblastoma Cells Without Affecting Tumor Frequency - Ceccarelli, Manuela; D'Andrea, Giorgio; Micheli, Laura; Tirone, Felice (Frontiers in Oncology, 2020)
About 30% of medulloblastomas, a tumor of the cerebellum, arise from cerebellar granule precusor cells (GCPs) undergoing transformation, following activation of the Shh pathway. To study this process, we generated a new medulloblastoma model by crossing Patched1 heterozygous (Ptch1+/−) mice, which develop spontaneous Shh-type medulloblastomas, with mice lacking Btg1, a regulator of cerebellar development. In medulloblastomas developing in Ptch1+/− mice, deletion of Btg1 does not alter tumor and lesions frequencies, nor affect the proliferation of neoplastic precursor cells. However, in both tumors and lesions arising in Ptch1+/− mice, ablation of Btg1 increases by about 25% the apoptotic neoplastic precursor cells, as judged by positivity to activated Caspase-3. Moreover, although Btg1 ablation in early postnatal GCPs, developing in the external granule cell layer, leads to a significant increase of proliferation and decrease of differentiation, relative to wild-type, no synergy occurs with the Ptch1+/− mutation. However, Btg1 deletion greatly increases apoptosis in postnatal GCPs, with strong synergy between Btg1-null and Ptch1+/− mutations. That pronounced increase of apoptosis observed in Ptch1+/−/Btg1 knockout young or neoplastic GCPs may be responsible for the lack of effect of Btg1 ablation on tumorigenesis. This increased apoptosis may be a consequence of increased expression of Prmt1 protein that we observe in Btg1 knockout/Ptch1+/− medulloblastomas. In fact apoptotic genes, such as BAD, are targets of Prmt1. Moreover, in Btg1-null medulloblastomas we observed a two-fold increase of cells positive to CD15, which labels tumor stem cells, raising the possibility of activation of quiescent tumor cells, known for their role in long-term resistance to treatment and relapses. Thus, Btg1 appears to play a role in cerebellar tumorigenesis by regulating the balance between apoptosis and proliferation during medulloblastoma development, also influencing the number of tumor stem cells.